2015
DOI: 10.1016/j.carbon.2015.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of carbon byproducts for high-purity carbon nanocoil growth by suppressing catalyst collision

Abstract: Carbon nanocoils (CNC) are promising nanocarbon materials for application as functional composites such as electromagnetic wave absorbers. However, the suppression of carbon byproducts during CNC growth is necessary to obtain high purity CNCs with high yield. Here, we demonstrate a simple but efficient method for the reduction of carbon byproducts using a patterned thin film catalyst. Results show that the collision of tip catalysts of growing CNCs to the substrate or other CNCs inhibits the smooth growth of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…4a. It is found that the height of CNC layer continuously increased with growth time, and the maximum thickness of the CNC layer reaches 306 μm after the reaction for 6 h. This is the highest value compared with those reported recently [34][35][36][40][41][42]. It is noted that both curves of the yield and thickness versus time are well matched, suggesting that the carbon deposits are almost CNCs.…”
Section: Yield Of High-purity Cncssupporting
confidence: 55%
See 3 more Smart Citations
“…4a. It is found that the height of CNC layer continuously increased with growth time, and the maximum thickness of the CNC layer reaches 306 μm after the reaction for 6 h. This is the highest value compared with those reported recently [34][35][36][40][41][42]. It is noted that both curves of the yield and thickness versus time are well matched, suggesting that the carbon deposits are almost CNCs.…”
Section: Yield Of High-purity Cncssupporting
confidence: 55%
“…1 f. The enlarged image of the area indicated by the box in Fig. 1 f shows the morphology of by-product layer, which is mainly composed of carbon-containing catalytic metal particles [ 42 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations